PENGARUH PERHATIAN GURU TERHADAP MINAT BELAJAR IPA SISWA KELAS IV SDN 13 BIRU KABUPATEN BONE - Sudarto Sudarto; Muliadi Muliadi; Andi Silviani (Bajang Institute, 2022)
This study was a correlational study that aimedto determine whether thre was or there was not an influence of the teacher attention to interest in learning science of the fourthgrade students of SDN 13 Biru, Tanete Riattang District, Bone Regency. The research population was all fourthgrade students of SDN 13 Biru in totaling 63 people. Data collection was done by using a questionnaire. Data analysis techniques include: statistical analysis of simple linear regression and significance test. The results of the study, namely (1) the value of R square = 0,004 (42%) which means the contribution of the teacher's attention to the students' interest in learning science was 4%, and (2) the value of t count (11,95) > t table (2,002), so Ho was rejected and H1 was accepted. Conclusion: teacher's attention had a significant effect to interest in learning science.